Arms race between leaf rollers and parasitoids: diversification of plant‐manipulation behavior and its consequences. Issue 2 (1st May 2015) - Kobayashi, Chisato; Matsuo, Kazunori; Watanabe, Kyohei; Nagata, Nobuaki; Suzuki-Ohno, Yukari; Kawata, Masakado; Kato, Makoto
Abstract : Understanding the determinants of community structure remains a challenging ecological task; the plant–host insect–parasitoid community is a particularly important community because of its overwhelming biomass in terrestrial ecosystems. Some ecological and phylogenetic factors are determinants of community structure; however, the relative importance of these factors remains to be entirely elucidated because we cannot separately analyze individual factors. Here, we compared parasitoid communities among 23 weevil species. We demonstrated that the parasitoid community structures were significantly influenced by types of maternal plant manipulation and larval feeding, but not by the phylogeny of the host plant or weevil, which has diverse feeding niches even within closely related species, through maternal plant manipulation for immature weevils (e.g., shoot/petiole/seed borers, leaf miners, and leaf roll feeders). Weevil phylogenetic data indicate that although plant‐cutting behavior may have evolved as an adaptation to plant chemical defenses, some manipulation behaviors, such as cutting off plants with eggs or open and closed leaf roll construction, may be an innovative adaptation against parasitoids. However, we expect that an evolutionary arms race would exist between weevils with specific manipulations (e.g., constructing wrapped leaf rolls) and their specific parasitoids.